1977
DOI: 10.1139/v77-185
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of decarboxylation of some pyridinecarboxylic acids in aqueous solution. II

Abstract: Six 3-substituted picolinic acids were synthesized and decarboxylated in buffered aqueous solutions of ionic strength 1.0 at 150 and/or 95°C. 3-Amino-and 3-hydroxypicolinic acids appear to decarboxylate by initial protonation, but the others fit the requirements of the Hammick mechanism for picolinic acid decarboxylation. Both electron-withdrawing and electron-releasing 3-substituents accelerate decarboxylation in picolinic acids but inhibit decarboxylation in their anions. Acceleration in the acids is conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…QAPRTase is unique among PRTases in catalyzing a decarboxylation linked to phosphoribosyl transfer. From both model studies (21) and enzyme experiments (22), the decarboxylation appears likely to occur via a hypothetical "quinolinate mononucleotide" intermediate, which is pro- † Supported by NIH Grant GM48623. * To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…QAPRTase is unique among PRTases in catalyzing a decarboxylation linked to phosphoribosyl transfer. From both model studies (21) and enzyme experiments (22), the decarboxylation appears likely to occur via a hypothetical "quinolinate mononucleotide" intermediate, which is pro- † Supported by NIH Grant GM48623. * To whom correspondence should be addressed.…”
mentioning
confidence: 99%
“…Displacement of the 3-position fluorine with the morpholine at rt afforded carboxylic acid 5 , which upon heating underwent decarboxylation to afford 6 . Thermal decarboxylation of 2-picolinic acids is known, but proceeds at a considerably higher temperature without the amine substituent . It is noteworthy and useful (see below) that the selectivity of room temperature displacement with morpholine is 30:1 for the 3- over the 5-position fluorine atom due to the carboxylate directing the morpholine nucleophile similar to reported amine displacements of 2,4-difluoro­benzoic acids …”
mentioning
confidence: 53%
“…Thermal decarboxylation of 2-picolinic acids is known, but proceeds at a considerably higher temperature without the amine substituent. 10 It is noteworthy and useful (see below) that the selectivity of room temperature displacement with morpholine is 30:1 for the 3-over the 5-position fluorine atom due to the carboxylate directing the morpholine nucleophile similar to reported amine displacements of 2,4-difluorobenzoic acids. 11 Continuing the synthetic sequence from 6 (Scheme 2), a series of directed lithiations were carried out.…”
mentioning
confidence: 82%
“…The synthesis of 3-aminopicolinic acid has been described previously (2), as have the methods of measuring rates (2) and 13C kinetic isotope effects (12 …”
Section: Methodsmentioning
confidence: 99%
“…The preceding papers in this series reported that the pH dependence of the first-order rate constants isotope effect at all pH's, both of which criteria were satisfied (1,2). However, the pH-rate profiles for 3-hydroxy-and 3-aminopicolinic acids do not have maxima at their isoelectric pH's, so they were assumed to proceed by some mechanism other than [I].…”
Section: Introductionmentioning
confidence: 99%